Proper Names as a Target of Language Awareness - Luchtenberg, Sigrid (Language awareness, 1998)
This paper looks first at the value of proper names in language awareness education by demonstrating their role in various fields of linguistics. It then deals with the role of proper names in three different areas of German language education: German as a mother tongue, German as a foreign language, and the multicultural classroom. The study reveals the marginal role of proper names in German language classes, mainly restricted to historical aspects such as the origin of place names or family names, while communicative, pragmatic or cultural aspects are neglected. Consideration of the role of proper names in language education suggests that they lend themselves to a holistic approach, as is the aim in language awareness, for they cover grammar as well as cultural learning or critical language awareness. Proposals are made regarding the teaching of proper names in the context of language awareness education within the German curriculum.